2021
DOI: 10.1093/rb/rbab021
|View full text |Cite
|
Sign up to set email alerts
|

Microarchitecture of titanium cylinders obtained by additive manufacturing does not influence osseointegration in the sheep

Abstract: Large bone defects are a challenge for orthopedic surgery. Natural (bone grafts) and synthetic biomaterials have been proposed but several problems arise such as biomechanical resistance or viral/bacterial safety. The use of metallic foams could be a solution to improve mechanical resistance and promote osseointegration of large porous metal devices. Titanium cylinders have been prepared by additive manufacturing (3D printing/rapid prototyping) with a geometric or trabecular microarchitecture. They were implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Many studies on porous materials have been conducted recently, mainly on osseointegration [ 28 , 40 ]. Porous materials provide a larger specific surface area and access for cells, oxygen, and nutrients to improve the biocompatibility of materials and promote tissue integration [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on porous materials have been conducted recently, mainly on osseointegration [ 28 , 40 ]. Porous materials provide a larger specific surface area and access for cells, oxygen, and nutrients to improve the biocompatibility of materials and promote tissue integration [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a physiological porous structure may promote tendon fixation. Rony et al compared implants with trabecular microarchitecture and purely geometric microarchitecture and reported that the former did not show better osseointegration [ 40 ]. Therefore, it seems irresponsible to simply imitate the trabecular bone or tendon structure.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramics, polymers and metals are all the candidate materials to support bone regeneration. Typically, ceramics stimulate mineralization via mimicking the inorganic portion of natural bone [ 223 , 224 ], polymers work as the bone ECM via mimicking crosslinking of collagen fibrils [ 225 , 226 ], and metals provide the mechanical support sometimes [ 227 ].…”
Section: Applications Of Biomaterials In Tissue Regenerationmentioning
confidence: 99%
“…11,12 On the contrary, this concave micropore geometry exhibited no advantage over the orthogonal-patterned pores when tested on titanium (Ti) cylinders in vivo. 13 Other reports have disclosed no osteoconductive advantages of HA-based and β-TCP templates over plain polymers in vitro, or when implanted in calvarial defects in the rabbit, except when functionalized with BMPs. 14 Nevertheless, none of the aforementioned studies investigated whether the discrepancies in the amount of new bone regeneration might be attributable to variations in Ca release from the HA templates.…”
Section: ■ Introductionmentioning
confidence: 98%